2018
DOI: 10.1155/2018/6171760
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Assistive Limb Intervention in a Patient with Late Neurological Deterioration after Thoracic Myelopathy Surgery due to Ossification of the Ligamentum Flavum

Abstract: Purpose We evaluated improvements in gait after using the Hybrid Assistive Limb (HAL®) exoskeleton robot in a patient with late-onset neurological deterioration of lower extremity function after undergoing thoracic spine surgery for a myelopathy due to ossification of the ligamentum flavum. Case Presentation A 70-year-old man participated in ten 20 min sessions of HAL intervention, twice weekly for five weeks. The effects of each HAL session were evaluated based on changes in performance on the 10 m walk test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…The results showed improvements in a series of clinical scales such as 10MWT, BI, GARS-M, and WISCI II. All participants showed improvements in gait ability that were similar to those of previous reports concerning the use of HAL for spine disorders such as SCI [ 8 14 ], SDAVF [ 41 ], and OPLL [ 18 22 , 26 ]. It is noteworthy that participants in our study underwent surgery for various reasons such as spinal cord tumor, vascular disease, and bone degenerative disease.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results showed improvements in a series of clinical scales such as 10MWT, BI, GARS-M, and WISCI II. All participants showed improvements in gait ability that were similar to those of previous reports concerning the use of HAL for spine disorders such as SCI [ 8 14 ], SDAVF [ 41 ], and OPLL [ 18 22 , 26 ]. It is noteworthy that participants in our study underwent surgery for various reasons such as spinal cord tumor, vascular disease, and bone degenerative disease.…”
Section: Discussionsupporting
confidence: 85%
“…Another recent study demonstrated neuroplasticity induced by HAL treatment [ 16 , 17 ]. However, five case reports have focused on the efficacy of HAL therapy for postoperative thoracic ossification of the posterior longitudinal ligament (OPLL) [ 18 22 ]. These reports indicated that HAL was used as a last resort for gait recovery during the almost chronic phase of the postoperative state [ 21 , 22 ], and the authors recommended starting HAL-assisted training during the early stage following surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies on the application of HAL for postoperative gait rehabilitation of OPLL patients with thoracic myelopathy (10)(11)(12)(37)(38)(39), gait improvement is reported by comparing the state of the patient before starting and after finishing the entire robot-assisted intervention. However, this comparison hinders examination of the effect of the robot during the training per se, as well as how it differs from training without the robot.…”
Section: Introductionmentioning
confidence: 99%